Double-phase layered potassium ion battery positive electrode material as well as preparation method and application thereof

By adjusting the potassium content and doping transition metals, a potassium ion battery positive electrode material with a P3/O3 biphase layered structure was prepared, which solved the cycle stability problem caused by the structural phase change of the potassium ion battery positive electrode material, and achieved high capacity and High stability electrochemical properties and simplify the preparation process.

CN119419258APending Publication Date: 2025-02-11NORTHEASTERN UNIV AT QINHUANGDAO
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411570578.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The structural phase change of the positive electrode material of potassium ion battery leads to poor cycle stability during charging and discharging, and lithium resources are scarce, so finding alternative materials is an urgent need.

Method used

By adjusting the potassium content and doping transition metals, a potassium ion battery positive electrode material with a P3/O3 biphase layered structure was prepared. Combined with the high-temperature calcination preparation process, the process flow is simplified and the structural stability of the material is improved.

Benefits of technology

The high capacity and high stability of the positive electrode material of potassium ion battery is achieved, the preparation process is simplified, the cost is reduced, and the electrochemical performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419258A_ABST
    Figure CN119419258A_ABST
Patent Text Reader

Abstract

The invention provides a double-phase layered potassium ion battery positive electrode material and a preparation method and application thereof, the chemical general formula of the potassium ion battery positive electrode material is Kx (Mn0. 25Fe0. 25) 1-yCryO2, x is more than or equal to 0.3 and less than or equal to 0.5, and y is more than or equal to 0.85 and less than or equal to 0.95; the positive electrode material of the potassium ion battery has a P3 / O3 double-phase layered structure; the preparation method comprises the following steps: (1) weighing a potassium source, a manganese source, an iron source and a chromium source according to a molar ratio of K: Mn: Fe: Cr = 1.05 x: 0.25 (1-y): 0.25 (1-y): y, and carrying out ball milling to obtain precursor powder; (2) carrying out tabletting treatment on the precursor powder, and putting a pressed sheet into a porcelain boat; (3) calcining the porcelain boat in a muffle furnace; by adjusting the potassium content and regulating the doping of the transition metal, the prepared double-phase layered positive electrode material for the potassium ion battery has the advantages of high capacity and high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a dual-phase layered potassium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid development of renewable energy and the increasing demand for energy storage technology. Although lithium-ion batteries have been widely used in electric vehicles and portable electronic devices, with the gradual scarcity of lithium resources and price fluctuations, finding alternative materials and technologies has become a research focus. Potassium is an element with high abundance in the earth's crust. It exists naturally in a variety of minerals and is relatively easy to obtain and low in cost. Potassium-ion batteries use potassium ions as charge carriers, which can provide better electrochemical performance while reducing production costs. Therefore, potassium-ion batteries are regarded as the most promising alternative to lithium-ion battery energy storage systems.

[0003] However, the radius of potassium ions is relatively large, which leads to higher requirements for the structure of electrode materials in potassium ion batteries. Therefore, it is particularly important for potassium ion batteries to develop low-cost, high-performance cathode materials. Inspired by the layered transition metal oxide cathode materials in the field of lithium ion batteries, potassium-containing layered oxides have also aroused interest in the application of potassium ion batteries. According to the different positions occupied by transition metal ions, layered metal oxide potassium ion battery cathode materials can be divided into P3 type and O3 type. P3 type cathode materials show a higher voltage platform in potassium ion batteries, can provide good energy density, and have a relatively stable structure during the insertion and extraction of potassium ions, and can maintain a longer cycle life. O3 type cathode materials help to improve the charge and discharge rate of potassium ion batteries and have good structural stability. However, both P3 and O3 types of layered metal oxide potassium ion battery cathode materials will undergo complex structural phase changes during the charge and discharge process, which will have an adverse effect on the battery's cycle stability.

[0004] In the P3-type manganese-iron-based layered potassium-ion battery cathode material system, doping with appropriate transition metals can promote its structural transformation to O3 type. Therefore, adjusting the type and proportion of doped transition metals to construct a dual-phase composite layered metal oxide cathode material can effectively alleviate the above problems. Based on the structural constraint effect of the composite structure, the advantages of multiple elements can be combined to achieve the purpose of improving the structural stability of the cathode material. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention provides a dual-phase layered potassium ion battery positive electrode material and a preparation method and application thereof. By adjusting the potassium content and regulating the transition metal doping, a dual-phase layered potassium ion battery positive electrode material with the advantages of high capacity and high stability is prepared. The preparation method of the present invention has a simple process, and the electrochemical performance exhibited by the positive electrode material when applied to potassium ion batteries has great research value.

[0006] The technical solution of the present invention is as follows:

[0007] A dual-phase layered potassium ion battery cathode material, the general chemical formula of which is K x (Mn 0.25 Fe 0.25 ) 1-y Cr y O2, where 0.3≤x≤0.5, 0.85≤y≤0.95.

[0008] Preferably, the dual-phase layered potassium ion battery positive electrode material has a P3 / O3 dual-phase layered structure.

[0009] Preferably, the chemical formula of the dual-phase layered potassium ion battery positive electrode material is K 0.5 (Mn 0.25 Fe 0.25 ) 0.1 Cr 0.9 O2.

[0010] As a general inventive concept, the present invention provides a method for preparing a dual-phase layered potassium ion battery positive electrode material, comprising the following steps:

[0011] (1) Weighing a potassium source, a manganese source, an iron source, and a chromium source according to a molar ratio of K:Mn:Fe:Cr=1.05x:0.25(1-y):0.25(1-y):y and placing them in a ball mill for ball milling to obtain a precursor powder;

[0012] (2) pressing the precursor powder obtained in step (1) into tablets, and placing the pressed tablets into a porcelain boat;

[0013] (3) placing the porcelain boat of step (2) into a muffle furnace and calcining it in an air atmosphere to obtain a dual-phase layered potassium ion battery positive electrode material.

[0014] Preferably, in step (1), the potassium source is one or more of potassium carbonate, potassium bicarbonate, potassium citrate, potassium oxalate, and potassium acetate; the manganese source is one or more of manganese dioxide, manganese acetate, manganese oxalate, and manganese trioxide; the iron source is one or more of iron oxide, iron acetate, and ferroferric oxide; and the chromium source is one or more of chromium oxide and chromium acetate.

[0015] Preferably, in step (2), the pressure of the tableting process is 0.5-0.9 MPa, and the holding time is 1-3 min.

[0016] Preferably, in step (3), the heating rate of calcination is 5-15°C / min, the calcination temperature is 800-950°C, and the calcination time is 8-16h.

[0017] As a general inventive concept, the present invention provides the above-mentioned dual-phase layered potassium ion battery positive electrode material and the application of the dual-phase layered potassium ion battery positive electrode material prepared by the above-mentioned preparation method, specifically, using the dual-phase layered potassium ion battery positive electrode material to prepare a potassium ion battery positive electrode sheet;

[0018] The raw materials for preparing the positive electrode plate of the potassium ion battery include a dual-phase layered potassium ion battery positive electrode material, acetylene black, a binder and a solvent, and the mass ratio of the dual-phase layered potassium ion battery positive electrode material, acetylene black, a binder and a solvent is 6-8:0.7-1:0.7-1:5-10.

[0019] Preferably, the binder is polyvinylidene fluoride (PVDF), and the solvent is N-methyl-2-pyrrolidone.

[0020] Preferably, the preparation method of the positive electrode sheet of the potassium ion battery comprises the following steps: mixing the dual-phase layered potassium ion battery positive electrode material, acetylene black, a binder, and a solvent to obtain a slurry; and then coating the obtained slurry on an aluminum foil current collector at a coating amount of 0.7-0.9 mg / cm 2 ; After drying, a positive electrode plate for a potassium ion battery is prepared; and the positive electrode plate for a potassium ion battery is used to prepare a CR2032 button battery.

[0021] The beneficial technical effects of the present invention are:

[0022] 1. The dual-phase layered potassium ion battery positive electrode material K in the present invention x (Mn 0.25 Fe 0.25 ) 0.1 Cr y O2, 0.3≤x≤0.5, 0.85≤y≤0.95, with a P3 / O3 dual-phase layered structure. P3-type cathode materials show a higher voltage platform in potassium ion batteries and can provide good energy density. O3-type cathode materials help to improve the charge and discharge rate of potassium ion batteries and have good structural stability. Co-doping of manganese, iron and chromium can optimize the electrochemical properties of electrode materials in many aspects. Therefore, P3 / O3 dual-phase layered potassium ion battery cathode materials will show excellent structural stability.

[0023] 2. In the preparation of the dual-phase layered potassium ion battery positive electrode material, the present invention obtains a chemical formula of K by simply adjusting the potassium content (the actual amount of potassium used is 5% more than the theoretical calculation) and regulating the transition metal doping and applying an appropriate preparation method. x (Mn 0.25 Fe 0.25 ) 1-y Cr y The invention discloses a potassium ion battery positive electrode material with a P3 / O2 structure, and by adjusting the doping amount of transition metal, the obtained metal oxide has a P3 / O3 two-phase layered structure, thereby obtaining a potassium ion battery positive electrode material with excellent electrochemical performance. In addition, when preparing the potassium ion battery positive electrode material, the present invention performs tableting on the precursor powder, which can shorten the reaction distance of the ions and enhance the crystallinity of the material.

[0024] 3. For the positive electrode material of the potassium ion battery of the present invention, if the content of Mn and Fe is changed, the electrochemical performance of the positive electrode material of the potassium ion battery will decrease. For example, when the molar ratio of Mn to Fe is less than 1:1, that is, when the Mn content is less and the Fe content is more, the P3 pure phase cannot be generated, and there will be an iron oxide impurity phase, and the discharge capacity of the synthesized positive electrode material is low; when the molar ratio of Mn to Fe is greater than 1:1, that is, when the Mn content is more and the Fe content is less, the Jan-Taylor effect of the positive electrode material is very significant, which will reduce the cycle performance of the battery.

[0025] 4. Compared with the prior art, the raw materials used for the positive electrode materials prepared by the present invention are not limited to a single form, but are rich in variety, breaking the traditional pattern inherent in raw materials. The one-step high-temperature calcination method used in the present invention has a simple process and high controllability, and can save the early precursor preparation process (for example, hydrothermal method, solvent thermal method, pre-calcination method, etc.), greatly saving preparation cost and time.

[0026] In terms of raw material ratio and process parameters, the present invention finally determines the optimal parameters through verification of examples and comparative examples. For example, if a sufficient amount of chromium (y=0.85, 0.9 or 0.95) is added during the preparation process, a positive electrode material with a P3 / O3 dual-phase layered structure will be obtained. If a small amount of chromium (y=0.3, 0.5 or 0.7) is added, it will be a positive electrode material with a P3 single-phase layered structure. Therefore, if no chromium is added or the amount added is insufficient, a P3 single-phase layered structure positive electrode material will be obtained, but a P3 / O3 dual-phase layered structure positive electrode material cannot be obtained. Compared with the traditional P3 single-phase layered structure positive electrode material, the P3 / O3 dual-phase layered structure positive electrode material has excellent structural stability due to the introduction of the O3 phase and the synergistic effect of co-doping with manganese, iron and chromium.

[0027] 5. The present invention uses the prepared dual-phase layered potassium ion battery positive electrode material to prepare the battery positive electrode sheet, and uses the potassium sheet as the negative electrode. The assembled half-cell can provide satisfactory first-cycle discharge capacity and structural stability, which is sufficient to prove the feasibility of using P3 / O3 dual-phase layered metal oxide as the positive electrode material of potassium ion battery and has great research value. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The XRD pattern of the positive electrode material of the potassium ion battery prepared in Example 1 of the present invention;

[0029] Figure 2 This is a SEM image of the potassium ion battery positive electrode material prepared in Example 1 of the present invention;

[0030] Figure 3 This is a cycle performance diagram of the potassium ion battery positive electrode material prepared in Example 1 of the present invention;

[0031] Figure 4 XRD diagram of the positive electrode material for a potassium ion battery prepared in Example 2 of the present invention;

[0032] Figure 5 This is a SEM image of the positive electrode material for a potassium ion battery prepared in Example 2 of the present invention;

[0033] Figure 6 This is a cycle performance diagram of the potassium ion battery positive electrode material prepared in Example 2 of the present invention;

[0034] Figure 7 This is the XRD pattern of the positive electrode material for a potassium ion battery prepared in Example 3 of the present invention;

[0035] Figure 8 This is a SEM image of the positive electrode material for a potassium ion battery prepared in Example 3 of the present invention;

[0036] Fig. 9 This is a cycle performance diagram of the potassium ion battery positive electrode material prepared in Example 3 of the present invention;

[0037] Fig.10 The XRD diagram of the positive electrode material of the potassium ion battery prepared in Comparative Example 1 of the present invention;

[0038] Fig.11 This is a SEM image of the potassium ion battery positive electrode material prepared in Comparative Example 1 of the present invention;

[0039] Fig.12 This is a cycle performance diagram of the potassium ion battery positive electrode material prepared in Comparative Example 1 of the present invention;

[0040] Fig.13 This is the XRD diagram of the potassium ion battery positive electrode material prepared in Comparative Example 2 of the present invention;

[0041] Fig.14 This is a SEM image of the potassium ion battery positive electrode material prepared in Comparative Example 2 of the present invention;

[0042] Fig.15 This is a cycle performance diagram of the potassium ion battery positive electrode material prepared in Comparative Example 2 of the present invention;

[0043] Fig.16 This is the XRD diagram of the potassium ion battery positive electrode material prepared in Comparative Example 3 of the present invention;

[0044] Fig.17 This is a SEM image of the potassium ion battery positive electrode material prepared in Comparative Example 3 of the present invention;

[0045] Fig.18 This is a cycle performance diagram of the potassium ion battery positive electrode material prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0046] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Embodiment 1:

[0048] A dual-phase layered potassium ion battery cathode material, whose chemical formula is K 0.3 (Mn 0.25 Fe 0.25 ) 0.15 Cr 0.85 O2.

[0049] The method for preparing the dual-phase layered potassium ion battery positive electrode material in this embodiment comprises the following steps:

[0050] (1) Weigh potassium carbonate, manganese dioxide, iron oxide, and chromium oxide according to a molar ratio of K:Mn:Fe:Cr=0.315:0.0375:0.0375:0.85 and place them in an agate ball mill for ball milling to obtain a precursor powder;

[0051] (2) pressing the precursor powder obtained in step (1) into tablets at a pressure of 0.9 MPa for 3 min; placing the pressed tablets into a porcelain boat;

[0052] (3) placing the porcelain boat of step (2) into a muffle furnace and calcining it in an air atmosphere at a heating rate of 15° C. / min, a calcination temperature of 950° C., and a calcination time of 16 h to obtain a dual-phase layered potassium ion battery positive electrode material.

[0053] The dual-phase layered potassium ion battery positive electrode material in this embodiment is used to prepare a positive electrode plate for a potassium ion battery. The specific preparation steps are as follows:

[0054] Weigh the biphasic layered potassium ion battery positive electrode material K according to the mass ratio of 8:1:1:8 0.3 (Mn 0.25 Fe 0.25 ) 0.15 Cr 0.85 O2, acetylene black, polyvinylidene fluoride PVDF, N-methyl-2-pyrrolidone, after fully stirring the above materials to form a black viscous slurry, the obtained slurry is evenly coated on the vacuum-dried aluminum foil current collector, and the coating amount is about 0.8 mg / cm 2 After drying, the positive electrode sheet of the potassium ion battery can be prepared. The above experiments are all carried out in a glove box.

[0055] Then, a CR2032 button-type half-cell was assembled with the potassium sheet as the negative electrode and the potassium salt solution as the electrolyte, and the following electrochemical performance tests were carried out.

[0056] Cycle test: During the test, the battery is at room temperature, and then the loaded battery is mounted on the LAND battery test system, the charge and discharge voltage range is set to 1.5-3.9V, and the test current density is 20mA / g.

[0057] The XRD characterization of the positive electrode material of the potassium ion battery obtained in this example is as follows Figure 1 As shown, SEM characterization Figure 2 As shown, the 200-cycle performance is as follows Figure 3 shown.

[0058] Embodiment 2:

[0059] A dual-phase layered potassium ion battery cathode material, whose chemical formula is K 0.4 (Mn 0.25 Fe 0.25 ) 0.05 Cr 0.95 O2.

[0060] The method for preparing the dual-phase layered potassium ion battery positive electrode material in this embodiment comprises the following steps:

[0061] (1) Weigh potassium carbonate, manganese dioxide, iron oxide, and chromium oxide according to a molar ratio of K:Mn:Fe:Cr=0.42:0.0125:0.0125:0.95 and place them in an agate ball mill for ball milling to obtain a precursor powder;

[0062] (2) pressing the precursor powder obtained in step (1) into tablets at a pressure of 0.9 MPa for 3 min; placing the pressed tablets into a porcelain boat;

[0063] (3) placing the porcelain boat of step (2) into a muffle furnace and calcining it in an air atmosphere at a heating rate of 10° C. / min, a calcination temperature of 800° C., and a calcination time of 8 h to obtain a dual-phase layered potassium ion battery positive electrode material.

[0064] The dual-phase layered potassium ion battery positive electrode material in this embodiment is used to prepare a positive electrode plate for a potassium ion battery. The specific preparation steps are as follows:

[0065] Weigh the biphasic layered potassium ion battery positive electrode material K according to the mass ratio of 6:1:1:6 0.4 (Mn 0.25 Fe 0.25 ) 0.05 Cr 0.95 O2, acetylene black, polyvinylidene fluoride PVDF, N-methyl-2-pyrrolidone, after fully stirring the above materials to form a black viscous slurry, the obtained slurry is evenly coated on the vacuum-dried aluminum foil current collector, and the coating amount is about 0.8 mg / cm 2 After drying, the positive electrode sheet of the potassium ion battery can be prepared. The above experiments are all carried out in a glove box.

[0066] Then, a CR2032 button-type half-cell was assembled with the potassium sheet as the negative electrode and the potassium salt solution as the electrolyte, and the following electrochemical performance tests were carried out.

[0067] Cycle test: During the test, the battery is at room temperature, and then the loaded battery is mounted on the LAND battery test system, the charge and discharge voltage range is set to 1.5-3.9V, and the test current density is 20mA / g.

[0068] The XRD characterization of the positive electrode material of the potassium ion battery obtained in this example is as follows Figure 4 As shown, SEM characterization Figure 5 As shown, the 200-cycle performance is as follows Figure 6 shown.

[0069] Embodiment 3:

[0070] A dual-phase layered potassium ion battery cathode material, whose chemical formula is K 0.5 (Mn 0.25 Fe 0.25 ) 0.1 Cr 0.9 O2.

[0071] The method for preparing the dual-phase layered potassium ion battery positive electrode material in this embodiment comprises the following steps:

[0072] (1) Weigh potassium carbonate, manganese dioxide, iron oxide, and chromium oxide according to a molar ratio of K:Mn:Fe:Cr=0.525:0.025:0.025:0.9 and place them in an agate ball mill for ball milling to obtain a precursor powder;

[0073] (2) pressing the precursor powder obtained in step (1) into tablets at a pressure of 0.9 MPa for 3 min; placing the pressed tablets into a porcelain boat;

[0074] (3) placing the porcelain boat of step (2) into a muffle furnace and calcining it in an air atmosphere at a heating rate of 5°C / min, a calcination temperature of 850°C, and a calcination time of 12h to obtain a dual-phase layered potassium ion battery positive electrode material.

[0075] The dual-phase layered potassium ion battery positive electrode material in this embodiment is used to prepare a positive electrode plate for a potassium ion battery. The specific preparation steps are as follows:

[0076] Weigh the biphasic layered potassium ion battery positive electrode material K according to the mass ratio of 8:1:1:8 0.5 (Mn 0.25 Fe 0.25 ) 0.1 Cr 0.9 O2, acetylene black, polyvinylidene fluoride PVDF, N-methyl-2-pyrrolidone, after fully stirring the above materials to form a black viscous slurry, the obtained slurry is evenly coated on the vacuum-dried aluminum foil current collector, and the coating amount is about 0.8 mg / cm 2 After drying, the positive electrode sheet of the potassium ion battery can be prepared. The above experiments are all carried out in a glove box.

[0077] Then, a CR2032 button-type half-cell was assembled with the potassium sheet as the negative electrode and the potassium salt solution as the electrolyte, and the following electrochemical performance tests were carried out.

[0078] Cycle test: During the test, the battery is at room temperature, and then the loaded battery is mounted on the LAND battery test system, the charge and discharge voltage range is set to 1.5-3.9V, and the test current density is 20mA / g.

[0079] The XRD characterization of the positive electrode material of the potassium ion battery obtained in this example is as follows Figure 7 As shown, SEM characterization Figure 8 As shown, the 200-cycle performance is as follows Fig. 9 shown.

[0080] Comparative Example 1:

[0081] A layered potassium ion battery positive electrode material, whose chemical formula is K 0.3 (Mn 0.25 Fe0.25 ) 0.7 Cr 0.3 O2.

[0082] The method for preparing the layered potassium ion battery positive electrode material in this comparative example comprises the following steps:

[0083] (1) Weigh potassium carbonate, manganese dioxide, iron oxide, and chromium oxide according to a molar ratio of K:Mn:Fe:Cr=0.315:0.175:0.175:0.3 and place them in an agate ball mill for ball milling to obtain a precursor powder;

[0084] (2) pressing the precursor powder obtained in step (1) into tablets at a pressure of 0.9 MPa for 3 min; placing the pressed tablets into a porcelain boat;

[0085] (3) placing the porcelain boat of step (2) into a muffle furnace and calcining it in an air atmosphere at a heating rate of 15°C / min, a calcination temperature of 950°C, and a calcination time of 16h to obtain a P3 phase layered potassium ion battery positive electrode material.

[0086] The layered potassium ion battery positive electrode material in this comparative example is used to prepare a positive electrode sheet for a potassium ion battery, and the specific preparation steps are as follows:

[0087] Weigh the P3 phase layered potassium ion battery positive electrode material K according to the mass ratio of 8:1:1:8 0.3 (Mn 0.25 Fe 0.25 ) 0.7 Cr 0.3 O2, acetylene black, polyvinylidene fluoride PVDF, N-methyl-2-pyrrolidone, after fully stirring the above materials to form a black viscous slurry, the obtained slurry is evenly coated on the vacuum-dried aluminum foil current collector, and the coating amount is about 0.8 mg / cm 2 After drying, the positive electrode sheet of the potassium ion battery can be prepared. The above experiments are all carried out in a glove box.

[0088] Then, a CR2032 button-type half-cell was assembled with the potassium sheet as the negative electrode and the potassium salt solution as the electrolyte, and the following electrochemical performance tests were carried out.

[0089] Cycle test: During the test, the battery is at room temperature, and then the loaded battery is mounted on the LAND battery test system, the charge and discharge voltage range is set to 1.5-3.9V, and the test current density is 20mA / g.

[0090] The XRD characterization of the positive electrode material of the potassium ion battery obtained in this comparative example is as follows Fig.10 As shown, SEM characterization Fig.11 As shown, the 200-cycle performance is as follows Fig.12 shown.

[0091] Comparative Example 2:

[0092] A layered potassium ion battery positive electrode material, whose chemical formula is K 0.4 (Mn 0.25 Fe 0.25 ) 0.5 Cr 0.5 O2.

[0093] The method for preparing the layered potassium ion battery positive electrode material in this comparative example comprises the following steps:

[0094] (1) Weighing potassium carbonate, manganese dioxide, iron oxide, and chromium oxide according to a molar ratio of K:Mn:Fe:Cr=0.42:0.125:0.125:0.5 and placing them in an agate ball mill for ball milling to obtain a precursor powder;

[0095] (2) pressing the precursor powder obtained in step (1) into tablets at a pressure of 0.9 MPa for 3 min; placing the pressed tablets into a porcelain boat;

[0096] (3) placing the porcelain boat of step (2) into a muffle furnace and calcining it in an air atmosphere at a heating rate of 10° C. / min, a calcination temperature of 800° C., and a calcination time of 8 h; a P3 phase layered potassium ion battery positive electrode material can be obtained.

[0097] The layered potassium ion battery positive electrode material in this comparative example is used to prepare a positive electrode sheet for a potassium ion battery, and the specific preparation steps are as follows:

[0098] Weigh the P3 phase layered potassium ion battery positive electrode material K according to the mass ratio of 6:1:1:6 0.4 (Mn 0.25 Fe 0.25 ) 0.5 Cr 0.5 O2, acetylene black, polyvinylidene fluoride PVDF, N-methyl-2-pyrrolidone, after fully stirring the above materials to form a black viscous slurry, the obtained slurry is evenly coated on the vacuum-dried aluminum foil current collector, and the coating amount is about 0.8 mg / cm 2 After drying, the positive electrode sheet of the potassium ion battery can be prepared. The above experiments are all carried out in a glove box.

[0099] Then, a CR2032 button-type half-cell was assembled with the potassium sheet as the negative electrode and the potassium salt solution as the electrolyte, and the following electrochemical performance tests were carried out.

[0100] Cycle test: During the test, the battery is at room temperature, and then the loaded battery is mounted on the LAND battery test system, the charge and discharge voltage range is set to 1.5-3.9V, and the test current density is 20mA / g.

[0101] The XRD characterization of the positive electrode material of the potassium ion battery obtained in this comparative example is as follows Fig.13 As shown, SEM characterization Fig.14 As shown, the 200-cycle performance is as follows Fig.15 shown.

[0102] Comparative Example 3:

[0103] A layered potassium ion battery positive electrode material, whose chemical formula is K 0.5 (Mn 0.25 Fe 0.25 ) 0.3 Cr 0.7 O2.

[0104] The method for preparing the layered potassium ion battery positive electrode material in this comparative example comprises the following steps:

[0105] (1) Weigh potassium carbonate, manganese dioxide, iron oxide, and chromium oxide according to a molar ratio of K:Mn:Fe:Cr=0.525:0.075:0.075:0.7 and place them in an agate ball mill for ball milling to obtain a precursor powder;

[0106] (2) pressing the precursor powder obtained in step (1) into tablets at a pressure of 0.9 MPa for 3 min; placing the pressed tablets into a porcelain boat;

[0107] (3) placing the porcelain boat of step (2) into a muffle furnace and calcining it in an air atmosphere at a heating rate of 5°C / min, a calcination temperature of 850°C, and a calcination time of 12h; thereby obtaining a P3 phase layered potassium ion battery positive electrode material.

[0108] The layered potassium ion battery positive electrode material in this comparative example is used to prepare a positive electrode sheet for a potassium ion battery, and the specific preparation steps are as follows:

[0109] Weigh the P3 phase layered potassium ion battery positive electrode material K according to the mass ratio of 8:1:1:8 0.5 (Mn 0.25 Fe 0.25 ) 0.3 Cr 0.7 O2, acetylene black, polyvinylidene fluoride PVDF, N-methyl-2-pyrrolidone, after fully stirring the above materials to form a black viscous slurry, the obtained slurry is evenly coated on the vacuum-dried aluminum foil current collector, and the coating amount is about 0.8 mg / cm 2After drying, the positive electrode sheet of the potassium ion battery can be prepared. The above experiments are all carried out in a glove box.

[0110] Then, a CR2032 button-type half-cell was assembled with the potassium sheet as the negative electrode and the potassium salt solution as the electrolyte, and the following electrochemical performance tests were carried out.

[0111] Cycle test: During the test, the battery is at room temperature, and then the loaded battery is mounted on the LAND battery test system, the charge and discharge voltage range is set to 1.5-3.9V, and the test current density is 20mA / g.

[0112] The XRD characterization of the positive electrode material of the potassium ion battery obtained in this comparative example is as follows Fig.16 As shown, SEM characterization Fig.17 As shown, the 200-cycle performance is as follows Fig.18 shown.

[0113] From the XRD patterns of the positive electrode materials of potassium ion batteries obtained in Examples 1-3 and Comparative Examples 1-3, it can be seen that for the positive electrode materials K x (Mn 0.25 Fe 0.25 ) 1-y Cr y O2, 0.3≤x≤0.5, when y=0.85, 0.9 and 0.95, the prepared positive electrode material is a P3 / O3 two-phase layered structure, and when y=0.3, 0.5 and 0.7, the prepared positive electrode material is a P3 single-phase layered structure.

[0114] From the SEM images of the potassium ion battery positive electrode materials in Examples 1-3 of the present invention and Comparative Examples 1-3, it can be seen that the surfaces of the samples are smooth and the crystallinity is good. However, the grain size of the P3 / O3 dual-phase layered structure positive electrode material in Examples 1-3 is smaller than the grain size of the P3 single-phase layered structure positive electrode material in Comparative Examples 1-3. The smaller grain size has a better infiltration effect with the electrolyte, and will show better discharge capacity and cycle performance.

[0115] From the cycle performance diagrams of the potassium ion battery positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-3, it can be seen that the cycle stability of the positive electrode material with a P3 / O3 dual-phase layered structure is significantly higher than that of the positive electrode material with a P3 single-phase layered structure. This is because the P3 / O3 dual-phase layered structure has a larger interlayer spacing, which can better adapt to the potassium ion deintercalation reaction, increase the diffusion rate of potassium ions, and extend the cycle life of the battery.

[0116] The cycle performance test results are as follows:

[0117] In Example 1, at a current density of 20 mA / g and a voltage range of 1.5-3.9 V, the first cycle discharge capacity is 105 mAh / g, and the capacity retention rate is 76% after 200 cycles.

[0118] In Example 2, at a current density of 20 mA / g and a voltage range of 1.5-3.9 V, the first cycle discharge capacity is 107 mAh / g, and the capacity retention rate is 81% after 200 cycles.

[0119] In Example 3, the first cycle discharge capacity is 120 mAh / g at a current density of 20 mA / g and a voltage range of 1.5-3.9 V, and the capacity retention rate is 90% after 200 cycles.

[0120] The first cycle discharge capacity of Comparative Example 1 is 98 mAh / g at a current density of 20 mA / g and a voltage range of 1.5-3.9 V, and the capacity retention rate is 52% after 200 cycles.

[0121] The first cycle discharge capacity of Comparative Example 2 is 102 mAh / g at a current density of 20 mA / g and a voltage range of 1.5-3.9 V, and the capacity retention rate is 55% after 200 cycles.

[0122] The first cycle discharge capacity of Comparative Example 3 is 103 mAh / g at a current density of 20 mA / g and a voltage range of 1.5-3.9 V, and the capacity retention rate is 57% after 200 cycles.

[0123] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A dual-phase layered potassium ion battery positive electrode material, characterized in that: Its chemical formula is K x (Mn 0.25 Fe 0.25 ) 1- y Cr y O2, where 0.3≤x≤0.5, 0.85≤y≤0.

95.

2. The double-phase layered potassium ion battery positive electrode material according to claim 1, characterized in that: The dual-phase layered potassium ion battery positive electrode material has a P3 / O3 dual-phase layered structure.

3. The double-phase layered potassium ion battery positive electrode material according to claim 1, characterized in that: Its chemical formula is K 0.5 (Mn 0.25 Fe 0.25 ) 0.1 Cr 0.9 O2.

4. A method for preparing a dual-phase layered potassium ion battery positive electrode material as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Weighing a potassium source, a manganese source, an iron source, and a chromium source according to a molar ratio of K:Mn:Fe:Cr=1.05x:0.25(1-y):0.25(1-y):y and placing them in a ball mill for ball milling to obtain a precursor powder; (2) pressing the precursor powder obtained in step (1) into tablets, and placing the pressed tablets into a porcelain boat; (3) placing the porcelain boat of step (2) into a muffle furnace and calcining it in an air atmosphere to obtain a dual-phase layered potassium ion battery positive electrode material.

5. The preparation method according to claim 4, characterized in that: In step (1), the potassium source is one or more of potassium carbonate, potassium bicarbonate, potassium citrate, potassium oxalate, and potassium acetate; the manganese source is one or more of manganese dioxide, manganese acetate, manganese oxalate, and manganese trioxide; the iron source is one or more of iron oxide, iron acetate, and ferroferric oxide; and the chromium source is one or more of chromium oxide and chromium acetate.

6. The preparation method according to claim 4, characterized in that: In step (2), the pressure of the tableting process is 0.5-0.9 MPa, and the pressure holding time is 1-3 min.

7. The preparation method according to claim 4, characterized in that: In step (3), the heating rate of calcination is 5-15°C / min, the calcination temperature is 800-950°C, and the calcination time is 8-16h.

8. An application of a dual-phase layered potassium ion battery positive electrode material as claimed in any one of claims 1 to 3 and a dual-phase layered potassium ion battery positive electrode material prepared by the preparation method as claimed in any one of claims 4 to 7, characterized in that: Using the dual-phase layered potassium ion battery positive electrode material to prepare a positive electrode sheet for a potassium ion battery; The raw materials for preparing the positive electrode plate of the potassium ion battery include a dual-phase layered potassium ion battery positive electrode material, acetylene black, a binder and a solvent, and the mass ratio of the dual-phase layered potassium ion battery positive electrode material, acetylene black, a binder and a solvent is 6-8:0.7-1:0.7-1:5-10.

9. The use according to claim 8, characterized in that The binder is polyvinylidene fluoride, and the solvent is N-methyl-2-pyrrolidone.

10. The use according to claim 8, characterized in that The preparation method of the positive electrode sheet of the potassium ion battery comprises the following steps: mixing the dual-phase layered potassium ion battery positive electrode material, acetylene black, a binder and a solvent to obtain a slurry; and then coating the obtained slurry on an aluminum foil current collector at a coating amount of 0.7-0.9 mg / cm 2 ; After drying, a positive electrode plate for a potassium ion battery is prepared; and the positive electrode plate for a potassium ion battery is used to prepare a CR2032 button battery.

Citation Information

Cited By

  • High-air-stability medium-entropy potassium ion battery positive electrode material, preparation method thereof and potassium ion battery

    CN121964621A